2000
DOI: 10.1590/s1516-35982000000500003
|View full text |Cite
|
Sign up to set email alerts
|

Respostas da Tilápia do Nilo (Oreochromis niloticus) à atratividade e palatabilidade de ingredientes utilizados na alimentação de peixes

Abstract: RESUMO -Avaliaram-se as respostas da tilápia do Nilo à atratividade e palatabilidade de 14 ingredientes. O método utilizado foi de dupla escolha, comparando-se cada ingrediente peletizado à uma ração controle. Foram empregados quatro aquários (750 litros) contendo, cada um, três alevinos e dois comedouros instalados nos cantos direito e esquerdo, sendo registrados tempo decorrido entre colocação do ingrediente e chegada dos animais aos comedouros, freqüência de visitas aos comedouros, número de grânulos ingeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Pereira-da-Silva (1999) has shown that the fish can select the food to be consumed. Nile tilapia can select during feed intake with different ingredients (Pereira-da-Silva, 2000). Almaida-Pagan et al (2006) determined that sharpsnout seabream (Diplodus puntazzo) is also able to selfbalance and regulate the consumption of proteins, carbohydrates and lipids while Fortes-Silva et al (2010) detected preference for diets with different types of oil for Nile tilapia.…”
Section: Methodsmentioning
confidence: 99%
“…Pereira-da-Silva (1999) has shown that the fish can select the food to be consumed. Nile tilapia can select during feed intake with different ingredients (Pereira-da-Silva, 2000). Almaida-Pagan et al (2006) determined that sharpsnout seabream (Diplodus puntazzo) is also able to selfbalance and regulate the consumption of proteins, carbohydrates and lipids while Fortes-Silva et al (2010) detected preference for diets with different types of oil for Nile tilapia.…”
Section: Methodsmentioning
confidence: 99%
“…Other advantages of the dietary inclusion of bovine MBM, in addition to its nutritional content, are the improvement of feed odor, flavor, and texture, increasing feed palatability, as well as their safety, as it does not contain allergens or antinutritional factors, allowing its use for a wide range of livestock diets (Pereira-Da- Silva and Pezzato, 2000). This suggests that the partial replacement of soybean meal by bovine MBM in laying Japanese quail diets may be an alternative to ensure proper nutrition at a lower cost.…”
Section: Bovine Meat and Bone Meal As An Economically Viable Alternatmentioning
confidence: 99%
“…The hypothalamic centers, likely involved in eating behavior and satiety, can be stimulated by either intestinal satiety or metabolic factors, like levels of metabolites in the blood or changes in temperature (Botero, 2004). Moreover, it has been shown that fish have a preference for certain pellet shapes, textures, smells and tastes (Botero, 2004), and regulate the intake of some nutrients and ingredients (protein levels, different oils and protein sources, among others) through testing of self-balancing and food selection, bringing us ever closer to their behavior, feeding preferences and nutritional requirements (Pereira-da-Silva & Pezzato, 1999;Pereira-da-Silva & Pezzato, 2000;Pereira-da-Silva et al, 2004;Bordinhon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%